A microRNA meta-signature for pancreatic ductal adenocarcinoma. (April 2014) - Frampton, Adam E; Giovannetti, Elisa; Jamieson, Nigel B; Krell, Jonathan; Gall, Tamara MH; Stebbing, Justin; Jiao, Long R; Castellano, Leandro
<x xml:space="preserve">Abstract</x> Evaluation of: Ma MZ, Kong X, Weng MZ et al. Candidate microRNA biomarkers of pancreatic ductal adenocarcinoma: meta-analysis, experimental validation and clinical significance. J. Exp. Clin. Cancer Res. 32(1), 71 (2013). Due to its aggressive and late presentation, there is an urgent need for novel and reliable biomarkers for the diagnosis and prognostication of pancreatic ductal adenocarcinoma (PDAC). MiRNAs have been extensively profiled in PDAC tissues, biopsies, blood samples and other biofluids and their expression levels compared to normal and chronic pancreatitis (CP) specimens in order to identify the most relevant candidates. Consolidation of these activities has not been attempted until now. The evaluated meta-review by Ma et al. helps to define the use of miRNAs as biomarkers for detecting this tumor-type and predicting survival outcomes in PDAC. Based on frequency and consistency between microarray studies, they identified a miRNA meta-signature for recognising PDAC: upregulation of miR-21, 23a, 31, 100, 143, 155, and 221; with downregulation of miR-148a, 217 and 375. Furthermore, they validated high miR-21, high miR-31 and low miR-375 tumoural expression as independently prognostic for poor overall-survival (OS; n = 70).